2015
DOI: 10.1126/science.aaa8651
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of an antibody that neutralizes dengue virus type 2 by locking E protein dimers

Abstract: There are four closely-related dengue virus (DENV) serotypes. Infection with one serotype generates antibodies that may cross-react and enhance infection with other serotypes in a secondary infection. We demonstrated that DENV serotype 2 (DENV2)–specific human monoclonal antibody (HMAb) 2D22 is therapeutic in a mouse model of antibody-enhanced severe dengue disease. We determined the cryo–electron microscopy (cryo-EM) structures of HMAb 2D22 complexed with two different DENV2 strains. HMAb 2D22 binds across vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
227
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(251 citation statements)
references
References 37 publications
9
227
1
2
Order By: Relevance
“…Like E16, MAb CR4354 inhibits WNV at a postattachment step and can inhibit virus fusion with synthetic liposomes (59,170). The structure of the CR4354 Fab bound to WNV revealed a discontinuous epitope that spanned neighboring E proteins, suggesting that this MAb and others that bind complex quaternary epitopes might block fusion by cross-linking E proteins on the virion (61,(170)(171)(172). While the multiple-hit hypothesis assumes that neutralization is a reversible process (181), in some cases, antibody binding results in an irreversible change in virion infectivity that persists upon the reversal of binding.…”
Section: Mechanisms Of Neutralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Like E16, MAb CR4354 inhibits WNV at a postattachment step and can inhibit virus fusion with synthetic liposomes (59,170). The structure of the CR4354 Fab bound to WNV revealed a discontinuous epitope that spanned neighboring E proteins, suggesting that this MAb and others that bind complex quaternary epitopes might block fusion by cross-linking E proteins on the virion (61,(170)(171)(172). While the multiple-hit hypothesis assumes that neutralization is a reversible process (181), in some cases, antibody binding results in an irreversible change in virion infectivity that persists upon the reversal of binding.…”
Section: Mechanisms Of Neutralizationmentioning
confidence: 99%
“…More critically, the number of accessible epitopes on the intact infectious virion provides the "denominator" for this relationship, as epitope accessibility ultimately governs the number of antibody molecules capable of binding the virus particle at saturation. Antibodies may bind epitopes defined by amino acid contacts from a single viral structural protein (167) or engage residues found on adjacent proteins or carbohydrates (61,(110)(111)(112)(113)(168)(169)(170)(171)(172). Complex or quaternary epitopes have been defined for many viruses, including flaviviruses (see below).…”
Section: Neutralization By the Numbersmentioning
confidence: 99%
“…The B-B′ dimer moves to a higher radius and the E proteins dissociate from each other. A study of an antibody, which traps a transitional stage of this motion 11 , suggests that the A-C′ dimer probably moves to a higher radius before the B-B′ dimer 11 . In the ZIKV structure, the possible network of interactions around the five-fold vertex between the five A-C′ dimers may result in tighter packing that prevents this structural transition.…”
mentioning
confidence: 99%
“…4 in (37)). For an IgG Ab, we found that the connectivity between the two Fabs is well approximated by a linker of [16][17][18] residues. The range of p(d 0 ) associated with the N AA values used in our application can be found in the Section F in the Supporting Material.…”
Section: Bivalent Binding Of Igg Absmentioning
confidence: 95%
“…For example, the DENV Ab 1F4 was found to bind exclusively to epitopes along the twofold and fivefold axis of symmetry of the viral envelope, with a total stoichiometry of 120 Abs (17); the DENVAb 2D22 was found to have a maximum stoichiometry of 180 Abs while binding to epitopes along all three axes of symmetry (18); and the DENV Ab 5J7 was found to have a stoichiometry of 60 Abs, binding to epitopes along only the threefold axis of symmetry (19). Reasons for the observed variations in binding stoichiometry and epitope occupancy are typically attributed to relatively small conformational differences between symmetry-related epitopes that interfere with Ab binding or alter epitope accessibility.…”
Section: Introductionmentioning
confidence: 99%